A cadaveric investigation of the radial artery origin and its anatomical variations - Aleisha J. Singh; Rohen Harrichandparsad; Lelika Lazarus (Translational Research in Anatomy)
Introduction: According to standard anatomical description, the radial artery typically originates as one of two terminal branches of the brachial artery within the cubital fossa. Despite the common embryological process of the upper limb arteries, there are anatomical variations in the origin of the radial artery such as the radial artery originating from the axillary artery or from the brachial artery in the arm. The present study aimed to investigate the origin of the radial artery within a select adult cadaveric South African sample. Methods: A total of thirty adult cadaveric specimens (n = 60 upper limbs) were dissected at the University of KwaZulu-Natal (BREC/00006978/2024). Results: The radial artery originated from the brachial artery in the cubital fossa as per standard anatomical description in 90 % of the upper limb specimens. In 10 % of the sample, the aberrant radial artery originated from the axillary artery (four unilaterally, and one bilaterally in an 80-year-old male cadaver). The aberrant radial arteries originated an average 172 ± 20.81 mm above the inter-epicondylar line of the humerus, with external and internal diameters of 5.45 ± 1.71 mm, and 3.10 ± 0.70 mm respectively. Conclusion: This study reports an incidence of 10 % of the sample in which the radial artery originated from the axillary artery. Knowledge of the variations in the origin of the radial artery within this select South African population may assist the clinician during coronary and neuro-interventional procedures.